Development of Sports Psychology Research and Athlete Performance in Reputable International Journals: Bibliometric Analysis - Putu citra Permana Dewi; Yasep Setiakarnawijaya; Kadek Dian Vanagosi; Lusiana; S.M. Fernanda Iragraha (Gladi : Jurnal Ilmu Keolahragaan, 2023)
This study aims to be able to map the scope of sports psychology research on the Scopus scientific article database. The research focus to describe the thematic areas that most attract the attention of academics, to analyze the development of research on sports psychology which is associated with athlete performance. This research method is descriptive quantitative with a bibliometric approach, assisted by Publish or Perish and VosViewers software. Research sample from the last two decades (2002-2022). Through the keywords "sports psychology" and "performance" in the "article title" found 59 articles. The results of the study show that research trends regarding sports psychology and athlete performance have increased. The fields that have most attracted the attention of academics are sport psychology, applied sport psychology, ethics, and athletic performance. The most frequently discussed topics are sport psychology, performance excellence, and applied sport psychology. Meanwhile burnout, athlete, exercise, ethics, mental skills, performance, talent, and expertise are topics that are rarely discussed. More in-depth research on topics that are rarely discussed can be carried out by other researchers.